On Marriage and Family: Classic and Contemporary Texts - Levering, Matthew (Rowman & Littlefield Publishers, 2005)
Marriage as an institution faces many challenges today. This volume presents essential wisdom from the 2000 year-old Christian tradition that is as true and valuable today as it always was. The readings present positive resources for understanding the sacrament of marriage as a beautiful and sacred Christian vocation, a context in which difficult times can be worked through with grace. Marriage also involves family, even if the couple has no children. In marrying a spouse, one marries his or her whole family. The readings embrace family life as well. Levering introduces historically arranged texts from Christian saints and spiritual leaders describing the nature and value of marriage, offering counsel about how to live out marriage as part of a life of faith, or depicting their own experience of family life. This volume has much to offer married couples, people preparing for marriage, and classroom study of marriage and family.